PENGEMBANGAN MEDIA PEMBELAJARAN E-KOMIK PADA MATERI TEOREMA PYTHAGORAS DI SMPN 4 LUBUK SIKAPING - Septy Febria Mariska; Zulfitri Aima; Hamdunah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low interest and motivation of students in participating in mathematics learning, especially in the Pythagorean theorem material, is the background for conducting this research. One effort that can be made to overcome this problem is through the development of interesting and contextual learning media, such as e-comics which combine visual elements and dialogue. This research aims to develop e-comic learning media on Pythagorean theorem material that meets valid and practical criteria.  The research method used is research and development (Research and Development) with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, Evaluation. However, this research is limited to the stage of testing the validity and practicality of the media. The research subjects were class VIII students at SMPN 4 Lubuk Suhuing, Pasaman Regency. The instruments used were validation questionnaires by material experts and media experts, as well as practicality test questionnaires by teachers and students. The results of the research show that the e-comic media developed obtained a validity level of 95.53% in the very valid category. Meanwhile, the practicality test results show an average percentage of 87.79% in the very practical category. Based on these results, it can be concluded that e-comic learning media on the Pythagorean theorem material is suitable for use in the learning process because it meets the valid and practical criteria. The implication of this research is that e-comics can be used as an interesting alternative learning media to increase students' interest and understanding in learning mathematics.